Investigation of the electrochemical behavior of mesalazine on boron-doped diamond electrode - Štěpánková, Michaela; Šelešovská, Renáta; Janíková, Lenka; Chýlková, Jaromíra (BEST Servis, 2016)
The possibility of application of boron-doped diamond electrode (BDDE) for voltammetric analysis of anti-inflammatory drug mesalazine has been investigated. Cyclic voltammetry was used for study of the voltammetric behavior of mesalazine depending on pH of supporting electrolyte and scan rate. It was found that it provides one oxidation peak on BDDE and the highest current response was observed in Britton-Robinson buffer of pH 7.0. Square wave voltammetry was applied for mesalazine determination and low limit of detection was reached 6.96×10−7 mol L−1. Finally, the proposed method has been successfully used in the analysis of the drug in commercial tablet form.
Studium voltametrického chování mesalazinu na borem dopované diamantové elektrodě
Keywords: Boron-doped diamond electrode; Voltammetry; Mesalazine; Determination; Borem dopovaná diamantová elektroda; voltametrie; mesalazin; stanovení